Impact of nutritional support on mortality among critically ill patients with different nutritional risks: a systematic review with meta-analysis - Bao, Lingling; Wang, Youquan; Li, Yuting; Zhang, Deyou; Li, Hongxiang (Frontiers in Nutrition, 2025)
BackgroundTo identify appropriate nutritional support strategies for critically ill patients with different levels of nutritional risk.MethodsA systematic search of PubMed, MEDLINE, Cochrane Library, and Embase was conducted from database inception to 19 May 2025, which included critically ill patients classified into high risk (5–9) and low risk (0–4) groups based on the modified Nutrition Risk in the Critically Ill (mNUTRIC) score. Data on study characteristics, patient demographics, and nutritional support details were extracted. The primary outcome was all-cause mortality following nutritional support stratified by nutritional risk among critically ill patients. A meta-regression analysis was performed to assess the influence of covariates on effect sizes and to identify potential sources of heterogeneity. Trial sequential analysis (TSA) was conducted to evaluate the robustness and reliability of the pooled effect estimates.ResultsEleven eligible trials, comprising a total of 7,442 participants, were included in this systematic review. The meta-analysis demonstrated that high nutritional risk was significantly associated with increased mortality (OR: 2.26, 95% CI: 1.80–2.83, p < 0.0001). Adequate energy intake was associated with a significantly lower 28-day mortality among patients at high nutritional risk (OR: 0.60, 95% CI: 0.38–0.94, p = 0.03). However, in randomized controlled trials, adequate energy support did not reduce 28-day mortality (OR: 1.09, 95% CI: 0.74–1.60) or 90-day mortality (OR: 1.03, 95% CI: 0.87–1.23) in high-risk patients.ConclusionThe mNUTRIC score is a validated prognostic tool in critically ill patients, but its effectiveness in guiding energy support remains limited.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42020188064, Identifier: CRD42020188064.